If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6x + -4 = 7 Reorder the terms: -4 + 5x + 6x = 7 Combine like terms: 5x + 6x = 11x -4 + 11x = 7 Solving -4 + 11x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 11x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + 11x = 7 + 4 11x = 7 + 4 Combine like terms: 7 + 4 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| 5y+2(y-8)=4(y-1)-3 | | (2x+9)-(4x+7)-6x=76 | | 156=6x+3(5x-18) | | 7x+146+x+48+65=147 | | 3-a=2a+7 | | 5z-3y+2x=5 | | -8y-8=3y+14 | | 3x-7=3(x-4)+1 | | (5a+9b-10c)+3(-6a+7c)= | | 8x+132=16x-12 | | 35+(.10)X=25+(.15)X | | -4=-2w | | 7x+5(x+18)=150 | | 11-3(2x+5y)= | | 36q^2-25=0 | | -7+7(6-1)=-3n-14 | | 6x+2=-3+4x+9 | | X^3+2x=25x+50 | | 150=7x+3(7x-6) | | -X+2=-22 | | 5y(2y-5)-5y=5(y-5)-9 | | 36x=72+26x | | 6x+1=2x^2 | | 3x^2-3x+60=0 | | (2x+10y-16)+(7x-8y+10)= | | (2x-27)=(x+2) | | x+2y+x-8y=180 | | y=2x^2-x+5 | | 3t=y | | 189=7x+7(4x-3) | | -8(x-8)=-4(4-4x) | | -5(3x+8)-5=20 |